COMPARATIVE LC-MS PROFILE OF THE THREE SPECIES HYPERICUM HOOKERIANUM, HYPERICUM MYSORENSE AND HYPERICUM WIGHTIANUM - NARAYANAN RAVISANKAR; JERRINE JOSEPH (International Journal of Pharma and Bio Sciences, 2015)
The genus Hypericum consists of both advanced and primitive tribes and taxa containing a complex mixture of secondary metabolites many of which are still being investigated. In the present study, we analyzed the methanol extracts of three Hypericum species (H.hookerianum, H.mysorense, and H.wightianum) of the Palni hills in southern India for the presence of bioactive hypericin and hyperforin and found characteristic discrimination of the three species based on LC-MS profiles. We report for the first time that H.mysorense lacks both these metabolites, H.wightianum contains only hypericin while H.hookerianum contains both the metabolites.